SAE Technical Paper Series 2007
DOI: 10.4271/2007-01-3110
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Uncertainty Quantification for Radiation Analysis Tools

Abstract: Recently a new emphasis has been placed on engineering applications of space radiation analyses and thus a systematic effort of Verification, Validation and Uncertainty Quantification (VV&UQ) of the tools commonly used for radiation analysis for vehicle design and mission planning has begun. There are two sources of uncertainty in geometric discretization addressed in this paper that need to be quantified in order to understand the total uncertainty in estimating space radiation exposures. One source of uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this paper, we focus on the distribution of target points within the effective dose tissues and use the 968 ray distribution used by Anderson et al (2007). The distribution is depicted in Fig.…”
Section: Numerical Target Point Distribution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we focus on the distribution of target points within the effective dose tissues and use the 968 ray distribution used by Anderson et al (2007). The distribution is depicted in Fig.…”
Section: Numerical Target Point Distribution Methodsmentioning
confidence: 99%
“…These two gaps (limited use of available human phantoms and target point selection) create potentially large uncertainties that need to be addressed. Anderson et al (2007) have provided one of the few uncertainty estimates for a portion of this process by examining spatial discretization in the interpolation databases and angular discretization in the ray distributions. It was found that 512 rays were sufficient for the lunar lander and habitat studied, and that for solar particle events (SPE), at least 20 approximately log-distributed spatial grid points were necessary to provide sufficient accuracy in the interpolation database.…”
Section: Introductionmentioning
confidence: 99%